Innovation of biochemistry learning media in higher education with android-based booklets - Nirmala, Wa; Bahalwan, Farida; Mahmudah, Rafiah; Sampulawa, Sriyati; Kasliyanto (Journal of Education and e-Learning Research, 2025)
This study aimed to produce valid, practical, and effective Android-based booklet media in Biochemistry learning. This type of research is development research (R&D) using the 4-D model. The samples used were validators consisting of media, material, and language experts, as well as all students of the biology education and chemistry education study programs at Universitas Darussalam Ambon, offering Biochemistry courses. The data were collected using validation sheets, questionnaires, and tests. The results showed that the Android application, namely Biomol, could be used by students in the biochemistry learning process. Based on the tests, a validity index of 0.84 was obtained in the valid category, a practicality value of 42.3 in the very practical category, and an effectiveness percentage of 70.39% in the quite practical category. The findings highlight that the Biomol application could significantly improve student learning outcomes. The novelty effect brought by Android-based learning media can further increase student interest in learning, particularly in chemistry subjects that include several abstract concepts. The results have implications for improving the quality of learning, flexibility, and students' digital competence in applying technology to address the challenges of education in the digital era.